BOUNDARY AND EXTERIOR OF A MULTISET TOPOLOGY - Debaroti Das; Juthika Mahanta (Journal of New Theory)
− The concepts of exterior and boundary in multiset topological space are introduced. Wefurther established few relationships between the concepts of boundary, closure, exterior and interiorof an M - set. These concepts have been pigeonholed by other existing notions viz., open sets, closedsets, clopen sets and limit points. The necessary and sufficient condition for a multiset to have anempty exterior is also discussed